(untitled) (Nigerian Journal of Physiological Sciences, 2025)
There is paucity of information on the relationship between resistin and cardiometabolic outcome among non-diabetic obese in Africa, especially Nigeria with a growing prevalence of obesity and cardiovascular events. This study aims to elucidate the relationship between serum resistin and insulin resistance among non-diabetic obese patients. This is a cross-sectional study, involving 100 non-diabetic obese and 100 non-obese Nigerians. Participants waist circumference, abdominal circumference and waist-hip ratio were measured alongside fasting blood glucose (FBG), lipid profile, remnant cholesterol and blood pressure. Serum resistin and insulin were determined with ELISA technique. Insulin resistance was assessed using the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) formula. Data was analyzed with Manny-Whitney test to compares the median of the observation between the two groups and chi-square for association test. Although FBG, serum insulin level and HOMA-insulin resistance (p<0.001) were significantly higher in the obese group, ditto for total cholesterol, LDL and remnant cholesterol, blood pressure and myocardial oxygen demand (MOD). However, circulatory resistin level in the obese group 1.63 (1.45-1.74) was comparable with the non-obese groups 1.63(1.52-1.70), and there was no correlation between resistin and insulin resistance and any anthropometrics indices Conclusion: Put together, resistin may not be a constant factor in the development of insulin resistance or obesity-related metabolic dysfunction in some obese subsets, hence the need to explore other potential adiponectin factors contributing to cardiometabolic outcomes in non-diabetic obese individuals in Nigeria